A Comparison of Thailand and Vietnam Regulations for Professional Accountants and Accounting Practices - Nomee, Charatsri (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2019)
The objective of this study was to compare the regulations for professional accountants and accounting practices between Thailand and Vietnam. The primary data used for this study was from laws, regulations for professional accountants, accounting practices and accounting standards in Thailand and Vietnam. The secondary data were collected from textbook, accounting journals, accountant related laws, research and online data. The data was then compared for similarities and differences. The results were that the qualification of accountants in Thailand was clearly defined, but was not so in Vietnam. Regarding the qualification of auditors, Vietnam did not define the age. The other qualifications were similarly defined. The two countries had clearly defined similar regulations concerning ethics for professional accountants. Penalties for professional accountants in Thailand was defined clearly, but was not so in Vietnam. A comparison of accounting practices in the two countries differed significantly, although there was a development of accounting standards based on international accounting standards. The practices varied due to the different accounting environments.